LOCAL COMMUNITY PARTICIPATION IN CITALUTUG TOURISM DESTINATION PROMOTION - Dosinaen, Alexander Silvius AmaTupe; Musafa, Musafa (PT. Altin Riset Publishing, 2023)
In promotions, participation is needed to attract people's creativity. In the field of facilities and infrastructure, community participation also influences development so that facilities and infrastructure can be updated from time to time. Local communities, in developing and promoting their tourist destinations, act as spearheads in the world of tourism, which also requires energy and hard work. Without active participation from the community, development and promotion will not be successful. To help realize good tourism development, good community participation is also needed. Because with good participation from the surrounding community, tourism business goals can be achieved as expected. The aim of this research is to determine the participation of local communities in promoting the Citalutug tourist destination. The research method used in this research is a qualitative phenomenological research method. This type of research was chosen by the researcher because it fits the topic of discussion in the research. In this research approach, the researcher used various information obtained in Citalutug tourism as well as experiences during the research to be used as a data source. The results of this research show that the community participation provided by them contributed to the promotion of the Citalutug tourist destination so that it was able to develop as it is today.